ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TRIGONOMETRI TIPE HIGHER ORDER THINKING SKILL DITINJAU DARI GENDER - Maya Mulyani; Dedi Muhtadi (Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to describe errors, factors that cause students to make mistakes made by students with high capability, medium, low, and the presence or absence of gender influence in solving Trigonometry question HOTS (Higher Order Thinking Skill) type.. This type of research is descriptive qualitative. The subjects of this study are six people, namely three male students and three female students, consisting of two highly capable students, two moderate capable students, and two low capable students. Data collection techniques in this study used the test, interview, and documentation methods. The data analysis technique is done in three stages, namely reduction data, presentation data, verification data, and conclusion. The analytical framework was developed based on Newman’s error category. The results of the study obtained five error types, namely (1) reading errors, (2) comprehension errors, (3) transformation errors, (4) process skills errors, (5) encoding errors. The most mistakes made by students are misunderstanding, transformation errors, and writing answers. General factors that cause these errors appeared because of students' lack of capability in interpreting the questions, level of understanding and students’ creativity who are low in identifying real problems in mathematical models. Research shows there are differences in the error type made by male and female subjects in solving problems which include five types of Newman's error. Keywords: Newman’s error, Trigonometry, HOTS, Gender